BEHAVIOR OF A LATERALLY LOADED PILE IN A PILE GROUP: A SIMPLIFIED ANALYTICAL STUDY - Uzair Amjad; Maaz Amjad; Irshad Ahmad; Muhammad Israr (Spectrum of Engineering Sciences, 2025)
Pile foundations are widely used to support superstructures where surface soils are weak or compressible. While vertical loads have traditionally been the main focus, piles also encounter substantial lateral loads in bridges, high-rise buildings, berthing structures, and offshore platforms. This study investigates the behavior of laterally loaded piles both as isolated single piles and as components of a pile group with varying center-to-center spacing. A comparative analysis is conducted using Allpile software to evaluate the bending moment response under lateral loading. The results demonstrate the significant influence of pile spacing on group interaction effects. At closer spacing (e.g., 3D), lateral moments increase due to load redistribution and shadowing effects. As spacing increases (up to 8D), the group effect diminishes and the pile behavior approaches that of a single isolated pile. This study provides practical insights into optimal pile group configurations and validates the importance of considering pile-soil-pile interaction in lateral load analysis.